1989
DOI: 10.1113/jphysiol.1989.sp017609
|View full text |Cite
|
Sign up to set email alerts
|

Changes of intracellular milieu with fatigue or hypoxia depress contraction of skinned rabbit skeletal and cardiac muscle.

Abstract: SUMMARY1. Maximal calcium-activated force (Fmax) and calcium sensitivity were markedly decreased in detergent-skinned fibres from skeletal and cardiac muscle by solutions that mimicked the total milieu changes associated with fatigue and hypoxia. Further experiments determined the relative contribution of each of the individual changes in milieu.2. Both Ca21 sensitivity and Fmax of skeletal and cardiac fibres were decreased with increased [H+] or inorganic phosphate (Pi). These effects were greater in cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
264
7
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(316 citation statements)
references
References 56 publications
44
264
7
1
Order By: Relevance
“…Concentrations of fast isoforms of myosin regulatory light chains (MLC) and, in particular, of the regulatory phosphorylatable isoforms known to modulate the rate of force development and of twitch maximal force at different initial tension levels [81][82][83], both of which are relevant to muscle function, were decreased. In vitro phosphorylation of MLC is known to increase calcium sensitivity thereby controlling the rate of force development and maximal force [84]. The drop of phosphorylatable isoforms and the decrement of phosphorylation of the acidic MLC f isoform found in elderly subjects, could impair performance.…”
Section: Agingmentioning
confidence: 99%
“…Concentrations of fast isoforms of myosin regulatory light chains (MLC) and, in particular, of the regulatory phosphorylatable isoforms known to modulate the rate of force development and of twitch maximal force at different initial tension levels [81][82][83], both of which are relevant to muscle function, were decreased. In vitro phosphorylation of MLC is known to increase calcium sensitivity thereby controlling the rate of force development and maximal force [84]. The drop of phosphorylatable isoforms and the decrement of phosphorylation of the acidic MLC f isoform found in elderly subjects, could impair performance.…”
Section: Agingmentioning
confidence: 99%
“…[Ca], (Godt & Nosek, 1989). Stern et al (1988), on the other hand, concluded that failure of systolic shortening during SI is accounted for mainly by a loss of the systolic increments in [Ca],.…”
Section: Discussionmentioning
confidence: 99%
“…Since glycolysis contributes to the energy supply during a short-term (6-10 s) cycling sprint (Gaitanos et al 1993;Nevill et al 1996), and in repeated cycling sprints (RCS), lactic acid accumulates within muscle, resulting in an increase in hydrogen ions (H + ) within muscle. The reduced intramuscular pH due to intramuscular accumulation of H + had been reported to decrease power output through impairment of the muscle contractile apparatus (Cooke et al 1988; Godt and Nosek 1989). However, a recent study using mammalian skinned muscle fibers (Pate et al 1995) has shown that the reduced intramuscular pH does not adversely affect the muscle contractile apparatus at physiological temperatures.…”
Section: Introductionmentioning
confidence: 97%